Entrepreneurial Behaviour of Dairy Farmers - Y.R. Patil, P.P. Wankhade, N.M. Kale and A.S. Kavthekar, (Indian Journal of Extension Education, 2017)
The study was conducted in Akola district of Maharashtra state with 100 dairy farmers. The results reveared thattwo third (67.00%) of dairy farmers belongs to medium entrepreneurial behaviour. Education, land holding, annualincome, economic motivation, scientific orientation, and attitude towards dairy farming shows positively and onlyage found negatively significant relationship with entrepreneurial behaviour. Whereas other variables like experiencein dairying, livestock possession and market orientation did not establish significant relationship with theirentrepreneurial behaviour.